PENTINGNYA PERANAN INTERNET DALAM DISTRIBUSI PEMASARAN PRODUK UMKM - Deasy Kartikasari (KOMPLEKSITAS: JURNAL ILMIAH MANAJEMEN, ORGANISASI DAN BISNIS, 2021)
Internet technology has created a new gateway in today's business landscape, Thomas L. Friedman revealed that the world today seems to be like a "flat" field, where everyone in the world can communicate and do business without being hindered by distance or time. The World is Flat, 2005). Businesses can easily Go International at a very low cost, by simply creating a website or just using social media. The research was carried out using qualitative methods, by means of observation and in-depth interviews. The object of research is several local Indonesian brands that have successfully adapted sales via online. Around 60% most of their active consumers are middle class living in urban areas such as Bandung, Jakarta, Surabaya, Makassar, Medan, Bali. Around 70% of creative entrepreneurs say that online channels will become the main communication platform in marketing, and off line stores will be complementary, due to their convenience, and ability to compare with other products in a short time.